Detection of changes in the ventral tegmental area of patients with schizophrenia using neuromelanin-sensitive MRI. Issue 5 (23rd March 2016) - Yamashita, Fumio; Sasaki, Makoto; Fukumoto, Kentaro; Otsuka, Kotaro; Uwano, Ikuko; Kameda, Hiroyuki; Endoh, Jin; Sakai, Akio
Abstract : The ventral tegmental area (VTA), one of the neuromelanin-containing dopaminergic nuclei in the midbrain, is closely related to the pathogenesis of schizophrenia, but its imaging findings remain unclear. Here, we investigated whether neuromelanin-sensitive MRI can detect alterations in the signals of the VTA of patients with schizophrenia. Neuromelanin-sensitive T1-weighted images at 3 T were obtained in 14 patients with schizophrenia and 22 healthy individuals. After signal inhomogeneity correction, brain signal rescaling of the images, and spatial normalization, signal intensity of the VTA and substantia nigra pars compacta (SNc) was automatically measured using the regions-of-interest constructed from the images of the healthy individuals. The normalized signal intensity of the VTA in patients with schizophrenia (median±quartile deviation, 998±10) was significantly decreased compared with that in healthy controls (1018±15) ( P =0.010), whereas that of the SNc was not significantly different between the groups (1093±6 and 1098±10, respectively, P =0.84). The VTA/SNc ratio was also significantly lower in patients with schizophrenia (0.916±0.007) than in the control participants (0.934±0.010) ( P =0.010). In addition, the scores of the Scale for the Assessment of Positive Symptoms showed an independent negative correlation with VTA signaling ( r =−0.69, P =0.012). Neuromelanin-sensitive MRI enables direct visualization of the selective signal attenuation in the VTA, which was correlated with positive symptoms, in patients with schizophrenia.